Implementation of Regional Regulation Number 2/2012 Toward Parking Service of Semarang City - Apriyanto Setyo Nugroho (Economics Development Analysis Journal, 2018)
Implementation of Local Regulation No. 2 of 2012 on parking services on the edge of public roads Semarang often found problems such as parking rates that are not in accordance with applicable regulations and parking attendants who use the parking ban area as a parking space The method used Qualitative Descriptive Analysis with purposive sampling as much 27 people showed the implementation of local regulation No. 2 of 2012 on public roadside parking service has not run with the maximum and the implementation found problems. The five factors influencing the implementation of the guidance of communication, availability of resources, public support, disposition of implementers, and the socio-economic conditions of politics are still not running maximally and it disrupts the implementation of the policy. The suggestions of this research include imposing heavier sanctions on parking attendants, improving the performance of the parking attendants so that in carrying out their duties can be in line with the prevailing regulations, improving communication through discussion in a forum, then the role of the community in guarding the implementation of the policy to be improved.